Biodegradable composite films from modified sugar palm (Arenga pinnata (Wurmb) Merr.) starch for food packaging applications - Sanyang, Muhammed Lamin (2015)
Rapid exhaustion of petroleum resources coupled with increasing awareness of global environmental problems related to the use of conventional plastics; are the main driving forces for the widespread acceptance of biopolymers as green materials. Biopolymers have attracted considerable attention due to their environmentally friendly and sustainable nature. Sugar palm is a multipurpose tree grown in tropical countries and it is regarded as a potential source for natural fibers and biopolymer. Sugar palm starch extracted from sugar palm tree can be utilized for preparing biodegradable starch based films. However, the inherent drawbacks associated with starch based films such as brittleness, poor water vapor barrier and high moisture sensitivity which in turn limit their wide application in the packaging industry. In order to address such drawbacks, three modification techniques were employed in this study: (1) plasticized with different plasticizers and concentration, (2) incorporated with another polymer or (3) reinforced with cellulose fibers to enhance functional properties of the resulting sugar palm based films. Consequently, sugar palm starch (SPS) films were successfully developed using solution casting method. The effect of different plasticizer types (glycerol (G), sorbitol (S) or glycerol-sorbitol combination (GS)) with varying concentrations (0 – 45 %) on the physical, mechanical, thermal and water barrier properties of SPS based films were evaluated. Regardless of plasticizer types, the tensile strength of plasticized SPS films decreased, whereas their elongation at break (E%) increased as the plasticizer concentrations were raised. However, the E% for G and GS-plasticized films significantly decreased at higher plasticizer concentration (45% w/w) due to antiplasticization effect of plasticizers. Change in plasticizer concentration showed insignificant effect on the thermal properties of S-plasticized films. The glass transition temperature of SPS films slightly decreased as the plasticizer concentration increased from 0 – 45 %. The plasticized films exhibited increased water vapor permeability values, irrespective of plasticizer types. Furthermore, the influences of glycerol-sorbitol plasticizer combination on the stability of functional properties of SPS based films with respect to storage time were investigated. Functional properties such as mechanical, thermal and water barrier properties were studied, in addition to crystallinity and moisture content of plasticized films after different storage time (1, 3 and 6 months) at constant temperature and relative humidity. The obtained results demonstrated significant changes on the functional properties of SPS films plasticized with only glycerol or sorbitol during storage. However, the combination of glycerol and sorbitol plasticizers helps to improve the stability, acceptability and shelf-life of SPS films. In addition, the development and characterization of environmentally friendly bilayer films from sugar palm starch (SPS) and poly (lactic acid) (PLA) were also investigated. The SPS-PLA bilayer films and their individual components were characterized for their physical,mechanical, thermal and water barrier properties. The incorporation of PLA layer significantly improved the mechanical, water vapor permeability as well as reduced the water uptake and solubility of bilayer films which was attributed to the hydrophobic characteristic of the PLA layer. Lastly, the effect of sugar palm derived cellulose loading on the physical, mechanical and water barrier properties of sugar palm cellulose fiber reinforced SPS composite films were evaluated. The addition of sugar palm cellulose from 1 to 10 % significantly improves the mechanical and water vapor permeability properties of the reinforced SPS composite films compared to virgin SPS films. Overall, the results obtained from the current research manifested that modified sugar palm starch with glycerol-sorbitol plasticizer, poly (lactic acid) in the case of SPS-PLA bilayer films, and the addition of sugar palm cellulose significantly increase the functional properties and enhances the suitability of SPS based films for food packaging. In conclusion, modified sugar palm starch based films are potential biodegradable materials for food packaging applications.